Attitudes toward lithium prescription among psychiatrists in Saudi Arabia: a cross-sectional study - Mohammad A. Alolayan; Mohammad A. Alolayan; Ahmad H. Almadani; Ahmad H. Almadani; Ghada K. Alrashed; Jamal Alothaim; Weam Hussein (Frontiers in Psychiatry)
BackgroundBipolar disorder (BD) is a mental illness with an estimated overall lifetime prevalence of 2.4% worldwide. Various pharmacological agents are available for treating BD, one of which is lithium. Lithium is commonly recommended as a first-line treatment during the maintenance phase of BD. However, prescribing patterns for mood disorders vary among countries, with notable regional differences in lithium use.MethodsThis cross-sectional study included 287 psychiatrists and psychiatry trainees in Saudi Arabia. A survey consisting of 22 multiple-choice questions was sent via WhatsApp to all participants. Data were collected between January and May, 2024.ResultsLithium was prescribed to BD patients by 72.5% of the participants. Most participants (70.7%) prescribed lithium to up to 25% of their patients. The primary reasons for not prescribing lithium were concerns about its adverse effects (64.8%), followed by the need for monitoring (53.7%), and the unavailability/shortage of lithium supply in Saudi Arabia (45.6%). Psychiatrists working in general hospitals (p=0.017) were more likely to prescribe lithium to patients with BD. In contrast, psychiatrists with limited experience or those who were unfamiliar with lithium treatment (p=0.001) were less likely to prescribe lithium.ConclusionThe use of lithium in Saudi Arabia is often influenced by concerns about its side effects, the need for monitoring, and product availability. Psychiatrists’ familiarity with lithium and the settings in which they practice are significant factors shaping prescribing behavior. Future efforts should focus on addressing the barriers to lithium prescription, including enhancing clinician training and improving access to lithium.